The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.6061/clinics/2012(08)07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arterial oxygen tension and cardiac output on venous saturation: a mathematical modeling approach

Abstract: OBJECTIVES:Hemodynamic support is aimed at providing adequate O2 delivery to the tissues; most interventions target O2 delivery increase. Mixed venous O2 saturation is a frequently used parameter to evaluate the adequacy of O2 delivery.METHODS:We describe a mathematical model to compare the effects of increasing O2 delivery on venous oxygen saturation through increases in the inspired O2 fraction versus increases in cardiac output. The model was created based on the lungs, which were divided into shunted and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
2
9
0
1
Order By: Relevance
“…It is possible that the magnitude of this phenomenon (here calculated as 4.9% points in SvO 2 per 100 mm Hg change in PaO 2 ) would be less prominent in the setting of diminished oxygen delivery (whether globally or regionally). As suggested previously by mathematical modeling, tissue hypoxia may cause excess dissolved oxygen to more rapidly diffuse to the mitochondrion, diminishing the magnitude of change in tPO 2 and therefore SvO 2 during hyperoxemia. Nonetheless, given these findings, SvO 2 cannot be viewed as a pure marker of the adequacy of DO 2 , but rather must be interpreted in the context of PaO 2 .…”
Section: Discussionmentioning
confidence: 64%
“…It is possible that the magnitude of this phenomenon (here calculated as 4.9% points in SvO 2 per 100 mm Hg change in PaO 2 ) would be less prominent in the setting of diminished oxygen delivery (whether globally or regionally). As suggested previously by mathematical modeling, tissue hypoxia may cause excess dissolved oxygen to more rapidly diffuse to the mitochondrion, diminishing the magnitude of change in tPO 2 and therefore SvO 2 during hyperoxemia. Nonetheless, given these findings, SvO 2 cannot be viewed as a pure marker of the adequacy of DO 2 , but rather must be interpreted in the context of PaO 2 .…”
Section: Discussionmentioning
confidence: 64%
“…Suggestion - Avoid systemic systemic vasodilators in refractory hypoxemia (they inhibit hypoxic vasoconstriction). ( 141 )…”
Section: Hemodynamic Changes and Hemodynamic Care In Patients On Invamentioning
confidence: 99%
“…Indeed, our recent work on patients with circulatory failure requiring vasopressors showed that PaO 2 could increase ScvO 2 and mixed venous oxygen saturation in a very substantial fashion (up to 10% in some patients)-more than the effect associated with changes in cardiac output 31 . Mathematical modelling also supports the fact that ScvO 2 could be affected by PaO 2 in a substantial fashion 32 . This novel concept is important because any increases in ScvO 2 due to an increase in PaO 2 would confound its associations with the cardiac output status of patients, rendering a 'good' ScvO 2 uninterpretable as a marker of adequate cardiac output or oxygen delivery 33 .…”
Section: Discussionmentioning
confidence: 62%